Key voting results in the Sejm and Senate of the Republic of Poland in the 1990s - Kwaśniewski, Jerzy (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Annex 2 rebuts the claim, spread in the media especially before 2020, that in 1993 "460 men banned abortion" in Poland, noting that both women and men voted on the legal protection of the unborn.It presents the results of four key votes: the Sejm's adoption of the Act of 7 January 1993 on family planning and the protection of the human foetus, the Senate's adoption of that Act, the Sejm's 1996 amendment introducing de facto abortion on request under the guise of "grave life circumstances," and the Senate's vote against that amendment, together with the Sejm's subsequent rejection of the Senate's opposition.The annex also cites John Paul II's Evangelium Vitae on the conscience of a parliamentarian faced with a choice between a more and a less permissive abortion law.